WEWENANG PEMERINTAH DIBIDANG PEMBINAAN NOTARIS DI JAWA TIMUR - Aulia, Farihan (Universitas Madura, 2018)
Functions and responsibilities of notary as public official, always have deals by law aspect. Notary must be give explain and testimony a content deed. In reality more mistake happen effect from notary negligence and effect from high value lobbying , now rarely happen. Tehe problem take from effect from impelementation of constitution no 2 Years 2014 by government, with law effect to law of notary and obstacles solution implementation controlling to notary. Aim of this research describe and analys uthority, government position to coach asa regulator stand for valid of constitution especially in east java area. Controlling not only done bya notary association buat also done by Minister of Law and Human Right. Initially based on constitution No,30 Years 2014 about notary occupation . After than have delegate to supervisory board and coaching , after that changed to constitution No . 2 years 2014 chapter 66 A, Law and human Right regulatory no M.02 PR.08. 10 years 2004, constitution of notary occupation give bordering authorized responsibility and prohibition which must be obey to as a notary. About this arranged in chapter 15,16, 17 and ethic profession of notary have controloed by supervisory board as regulated on chapter 67,68, 69 constituation No.30 years 2004. Step by step must be done by supervisory on handle control of obstacles and to coach notary as such as : a. supervisory board as MPD,MPN,MPW to hold on the job not alal have synergy, all this can do by to held law anylises seminar together and law workshop together.